THE RIGHT TO WORK IN THE CONDITIONS OF THE COVID-19 CRISIS: THEORETICALLY LEGAL DIMENSION - Denysenko, Viktoriya; Popov, Kostyantyn (Sworld-Us Conference proceedings, 2022)
The COVID-19 pandemic has had a profound impact on the labor market, leading to an increase in unemployment, underemployment and informal employment. Adherence to the principles of decent work, including health, safety, justice and social protection, has